Carrageenan-based antimicrobial bionanocomposite films incorporated with ZnO nanoparticles stabilized by melanin. (May 2019) - Roy, Swarup; Rhim, Jong-Whan
Abstract: Zinc oxide nanoparticles (ZnONP) were prepared by reacting zinc acetate with KOH using melanin as a capping agent, and used for the preparation of antimicrobial carrageenan-based nanocomposite films. The ZnONP capped with melanin (mZnONP) was stable and flake-like, while the control ZnONP without capping was rod-like. ZnONPs, whether capped or not capped with melanin, were evenly dispersed in the carrageenan matrix to form smooth and flexible nanocomposite films. The mZnONP incorporated composite film (Carr/mZnONP) exhibited a higher UV-blocking property at the expense of less transparency than the control ZnONP incorporated nanocomposite film (Carr/ZnONP). The Carr/mZnONP composite film also exhibited higher thermal stability with increased mechanical and water vapor barrier properties than the Carr/ZnONP composite film. Both nanocomposite films exhibited strong antibacterial activity against Gram-negative foodborne pathogenic bacteria, E. coli, but slight antibacterial activity against Gram-positive bacteria, L. monocytogenes . Graphical abstract: Image 1 Highlights: Zinc oxide nanoparticles (ZnONP) were produced using melanin as a stabilizing agent. Carrageenan/ZnONP composite films were prepared using a solution casting method. Incorporation of ZnONP increased the UV light barrier property. Mechanical and water vapor barrier properties were improved by the addition of ZnONP. Carrageenan/ZnONP composite film exhibited antibacterial activity against food-borne pathogens.